Monitoring RPM Engine Dan Temperature Minyak Pelumas Pada Genset Berbasis IoT - Ardi Setyo Hermawan; Kunto Eko Susilo (Universitas Sam Ratulangi, 2021)
Abstract — The use of technology has made human life easier. All sectors of life have merged with technology. As well as IOT (Internet Of Things) technology in the shipping sector. The shipping sector in Indonesia is quite important, because more than 70% of the area in Indonesia is oceans. One of them is